Peripheral blood and bone marrow cells cultivated in Novy-Mcneal-Nicolle medium for visceral leishmaniosis diagnosis revealed Rhodotorula fungemia in an AIDS patient with lymphoma - Paugam, Andre; Lebuisson, Agathe; Lortholary, Olivier; Baixench, Marie-Therese; Lanternier, Fanny (Clinical laboratory (Heidelberg), 2013)
Rhodotorula is a ubiquitous yeast that can infect immunocompromised patients. Here, we present the case of a 45-year-old patient with AIDS who developed a Rhodotorula mucilaginosa fungemia. The patient had a past history of visceral leishmaniasis (VL) and was hospitalised to receive chemotherapy for a B-cell lymphoma of the sinonasal cavities. The patient had no fever and no signs of VL. A systematic research for Leishmania by blood and bone marrow cultures was made and he received liposomal amphtotericin B (3 mg/kg in a single dose) to prevent a VL relapse. Rhodotorula fungemia was accidentally detected after 17 days of blood culture using a specific medium for leishmaniasis diagnosis. This long culture incubation time was probably facilitated by amphotericin B treatment. Rhodotorula is an emerging pathogen that may escape detection due its slow growth in culture.